Analisis Faktor-Faktor yang Mempengaruhi Pendapatan Nelayan di Pulau Kawaluso Kabupaten Kepulauan Sangihe - Costantein Imanuel Sarapil; Eunike Irene Kumaseh; Raemon Raemon; Ganjar Ndaru Ikhtiagung (ETNOREFLIKA: Jurnal Sosial dan Budaya, 2023)
This study aims to analyze the fishermen's level of household income in Kawaluso Island and the factors that affect the fishermen's income. This research was conducted in Kawaluso Island, Kendahe Sub District, Sangihe Islands Regency from July to September 2022. The data used is primary data obtained through interviews with fishermen using a questionnaire. Secondary data includes the data of population from BPS (Central Bureau of Statistics) of Sangihe Islands Regency, journals and other references. The sampling method used was a purposive sampling method, implemented through selecting fishermen in Kawaluso Island. This study used multiple regression methods where this study used multivariate with one matrix dependent variable. The multiple analytical methods were completed using the SPSS program. The catches together have a significant effect on the income of fishermen in Kawaluso Island, Kendahe Sub District, Sangihe Islands Regency. Age and catch simultaneously have a significant effect on fishermen's income on Kawaluso Island. The catch partially has a significant effect on the income of fishermen in Kawaluso Island. The fishermen's average income is IDR 3,000,000, so the fishing business for fishermen is a profitable business in Kawaluso Island.